Anti‐PD‐1 therapy redirects macrophages from an M2 to an M1 phenotype inducing regression of OS lung metastases. (7th May 2018) - Dhupkar, Pooja; Gordon, Nancy; Stewart, John; Kleinerman, Eugenie S.
Abstract: Osteosarcoma (OS) pulmonary metastasis translates into poor patient survival. The implication of PD‐1‐PD‐L1 pathway in the context of NK cells and/or macrophages in OS is unknown. We investigated the effect of anti‐PD‐1 in OS lung metastasis and the role of NK cells and/or macrophages in anti‐PD‐1 responses. A human LM7 OS mouse model was used. Immunohistochemistry for tissues (PD‐L1, caspase‐3, Ki‐67, NK cells, macrophages), and Western blotting for OS lung tumors (p‐Stat3, p‐Erk1/2) was performed. NK and macrophages were assessed using flow cytometry. NK cell and macrophage depletion were conducted using anti‐asialo GM1 and clodrosome, respectively. PD‐L1 expression was observed in human OS cells and OS patient lung metastases. Anti‐PD1 antibody led to a significant decrease in the number of OS lung metastases, enhanced tumor apoptosis, decreased tumor cell proliferation, and p‐STAT‐3/p‐Erk1/2 signaling blockade in OS lung tumors. NK cells and macrophages in OS lung tumors expressed PD‐1 and anti‐PD1 increased NK cell and macrophage tumor infiltration. Increased numbers of antitumor M1 macrophages and decreased pro‐inflammatory M2 macrophages were seen. NK depletion did not affect therapeutic effect of anti‐PD‐1, suggesting that NK cells were not directly involved. However, macrophage depletion significantly compromised anti‐PD1 efficacy, confirming their role in efficacy of anti‐PD‐1 against OS lung metastasis. Our findings suggest that OS lung metastases regression by anti‐PD1 can be attributed to activated tumor M1 macrophages and reduced M2 macrophages. Owing to the co‐relation of M1 macrophages with OS patient outcome, we provide a novel mechanism of PD‐1 blockade and a basis for future clinical trials for anti‐PD‐1 antibodies in OS. Abstract : PDL‐1 is expressed in human OS cells and OS patients, and PD‐1 expression is seen on NK cells and macrophages in OS lung metastatic tumors from mice. Anti‐PD1 leads to tumor cell apoptosis, decreased tumor cell proliferation and p‐STAT‐3 signaling, and regression of OS lung metastases, through activated M1 macrophages and reduced M2 macrophages infiltrating the tumors, thus making it a promising approach for OS lung metastasis therapy.